A critical study of the curcumin method for the determination of boron in plant material - Davidson, Raymond John (Rhodes University, Faculty of Science, Department of Chemistry, 1958)
Methods for the determination of boron are reviewed. A thorough investigation of the curcumin method was undertaken. Factors such as spectral absorption, boron volatilisation and the effects of pH, the stability of reagents and colour solutions, the drying of reaction products and the interference from certain elements, were investigated. A study of the efficiency of extracting boron from plant material using an ashing procedure is presented. The modified curcumin method for the determination of boron in plant material is described. The statistical accuracy and precision of the modified method is presented. The modified method was used to determine the boron content in citrus and pineapple leaf samples obtained from various parts of the Eastern Cape.
Keywords: Plants -- Nutrition; Boron; Turmeric